Persepsi Mahasiswa Universitas Esa Unggul dalam Pembelajaran Online di Media E-Learning - Eka Putri, Oktaviyanti Ramadhani; Natasha, Regina (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
e-learning, by Internet connection has become an inseparable part of life. Modern because it can help people do their activities more easily in many fields of work, including in education. Thus, many practitioners and educational institutions create learning to support their teaching and learning process. Online learning is also considered more practical to organize the teaching and learning process because it does not require a classroom to carry out these activities. So, teachers and students can create classes from different places. However, online learning faces several problems in its implementation, Student interaction and learning environment. Therefore, this study is intended to explore these problems based on student perceptions and the learning environment (Adijaya & Santosa, 2018) Previous research on (Martinez-Argüelles et al., 2010), emphasized the importance of collecting feedback from students to monitor the quality and standards of teaching, both in conventional learning and Elearning. (Bentley et al., 2012) student opinions about e-learning, which is an alternative to traditional classroom teaching and learning. This study was conducted because, with the advancement of technology, tools are available to enable it, therefore it is necessary to know the opinions of students about the idea of e-learning, as they are the main targets and beneficiaries of learning enabled by this technology. The results of the study showed that the majority of students considered e-learning to be an innovative idea and should be encouraged, however, only a few concerns such as fear of employer discrimination against those who learn through e-learning were found. It was also realized that hybrid learning, which is a combination of online learning and face-to-face learning (Mamattah, 2016)